Sulfoquinovosyl diacylglycerol synthase 1 impairs glycolipid accumulation and photosynthesis in phosphate-deprived rice. (24th June 2021) - Sun, Yafei; Song, Ke; Liu, Lu; Sun, Lijuan; Qin, Qin; Jiang, Tingting; Zhou, Bin; Zhu, Caihua; Xu, Guohua; Sun, Shubin; Xue, Yong
Abstract : OsSQD1 plays a key role in glycolipid accumulation and impairs photosynthesis in rice under Pi-deficiency. Abstract: Phosphate (Pi)-starved crops utilize phospholipids as a source for internal Pi supply by replacing non-phosphorus glycolipids. In rice, sulfoquinovosyl diacylglycerol synthase 1 (OsSQD1) functions as a key enzyme in the first step to catalyze sulfoquinovosyldiacylglycerol (SQDG) formation. Here we study differential expression of OsSQD1 in response to Pi, nitrogen, potassium, and iron-deficiencies in rice. Electrophoretic mobility shift assay suggested that OsSQD1 is regulated by OsPHR2 (Phosphate Starvation Response2), a MYB (v-myb avian myeloblastosis viral oncogene homolog) domain-containing transcription factor. The concentrations of different lipid species in ossqd1 knockout mutant demonstrated that OsSQD1 silencing increased the phospholipid content and altered fatty acid composition under Pi-deficiency. Moreover, OsSQD1 silencing reduces glycolipid accumulation under Pi-deficiency, and triggered the saturation of fatty acids in phospholipids and glycolipids treated with different Pi regimes. Relative amounts of transcripts related to phospholipid degradation and glycolipid synthesis were assessed to explore the mechanism by which OsSQD1 exerts an effect on lipid homeostasis under P-deficiency. Furthermore, OsSQD1 silencing inhibited photosynthesis, especially under Pi-deficient conditions, by down-regulating glycolipids in rice shoots. Taken together, our study reveals that OsSQD1 plays a key role in lipid homeostasis, especially glycolipid accumulation under Pi-deficiency, which results in the inhibition of photosynthesis.